Program Baca Tulis Al-Qur’an; Sebuah Habituasi Pendidikan Karakter Pada Anak Di Kecamatan Anjir Muara, Barito Kuala - Jumriani Jumriani; Muhammad Rezky Noor Handy; Bambang Subiyakto; Syaharuddin Syaharuddin; Nadlatul Izmi (Pendidikan IPS FKIP ULM, 2021)
Character education has an important role in forming a quality generation. One effort that can be made to instill character values in future generations is through reading and writing Al-Qur'an activities. This article aims to describe the habituation of character education through reading and writing Al-Quran program in Sei Ulak Canoco Village, Anjir Muara District, Barito Kuala Regency. This article was compiled from the results of community service carried out on October 13 and 25, 2020. In the results of the analysis part, researchers used literature studies from various sources and scientific journals. The results of the discussion described that reading and writing Al-Qur'an can be an activity to habituate children with applying religious teachings and forming religious characters. The Al-Qur'an reading and writing activities are carried out using a fun approach for children such as simple games and competitions. Therefore, reading and writing Al-Qur’an is a reflection that instilling a religious character can be done from childhood, until the end of his life.